2020
DOI: 10.3389/fmicb.2019.03090
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing-Independent Cellulase-Sensitive Pellicle Formation Is Critical for Colonization of Burkholderia glumae in Rice Plants

Abstract: Bacteria form biofilms as a means to adapt to environmental changes for survival. Pellicle is a floating biofilm formed at the air-liquid interface in static culture conditions; however, its functional roles have received relatively little attention compared to solid surface-associated biofilms in gram-negative bacteria. Here we show that the rice pathogen Burkholderia glumae BGR1 forms cellulase-sensitive pellicles in a bis-(3-5)cyclic dimeric guanosine monophosphate (c-di-GMP)-and flagellum-dependent, but qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Pellicle formation of B. glumae BGR1 was the first behavioral change observed in static culture [21]. The present study demonstrated that cells of B. glumae change genetic elements to The levels of c-di-GMP were elevated in the bspP null mutant BGP38 compared to those of wild-type BGR1 and the complementation strain BGP38C.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Pellicle formation of B. glumae BGR1 was the first behavioral change observed in static culture [21]. The present study demonstrated that cells of B. glumae change genetic elements to The levels of c-di-GMP were elevated in the bspP null mutant BGP38 compared to those of wild-type BGR1 and the complementation strain BGP38C.…”
Section: Discussionsupporting
confidence: 48%
“…Pellicle formation of B . glumae BGR1 was the first behavioral change observed in static culture [ 21 ]. The present study demonstrated that cells of B .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations